Sociodemographic profile of pterygium patients attending Government Medical College, Jammu, Jammu and Kashmir- a study from North India - Manhas, Angli; Gupta, Dinesh; Manhas, Rameshwar S.; Manhas, Gaurav S. (International Journal of Research in Medical Sciences, 2017)
Background: Pterygium is a fibrovascular wing or triangular shaped tissue that develops from the conjunctiva and encroaches on to the cornea. Methods: This prospective observational study was conducted at postgraduate department of Ophthalmology of GMC Jammu, Jammu and Kashmir, India. A total of 90 pterygium patients were selected to analyze various sociodemographic factors especially age, sex, residence, occupation, position etc. on the occurrence of this problem. Results: In the present study, out of 90 pterygium patients, 40% were in the age of 31-40 years followed by 24.44% in 41-50years, 60% were males whereas 66.67% belong to rural areas. The incidence was found to be maximum among farmers 35.56% followed by labourers 20%. The right eye was involved in 55.56% cases while majority 97.78% cases of pterygium were nasal. Progressive pterygium was found in 80% while 20% reported with atrophic pterygium. Conclusions: People who work outdoors are subjected to involuntary U.V. B exposure, dust. Workers must be aware of this and they must take appropriate precautions like wearing protective photochromatic glasses, caps etc.